Emergence of Genetic Diversity and Multi-Drug Resistant Campylobacter jejuni From Wild Birds in Beijing, China - Du, Juan; Luo, Jing; Huang, Jingjing; Wang, Chengmin; Li, Meng; Wang, Bojun; Wang, Bo; Chang, Han; Ji, Jianwei; Sen, Keya; He, Hongxuan (Frontiers in Microbiology, 2019)
Campylobacter jejuni (C. jejuni) is considered as an opportunistic zoonotic pathogen that may cause gastroenteritis in humans and other animals. Wild birds may be as potential vectors of C. jejuni around urban and suburban areas. Here, 520 samples were collected from 33 wild bird species in urban and suburban areas, Beijing. In total fifty-seven C. jejuni were isolated from 7 species. It was found that Nineteen (33.33%, 19/57) isolates were resistant to at least one of 11 antibiotics, especially streptomycin (36.84%) and four isolates resistant to all. Nineteen (33.33%, 19/57) isolates were multi-drug resistance. Multilocus sequence typing (MLST) analysis of the isolates showed that 36 different sequence types (STs) belonged to 4 Clonal complexes and unassigned. Twenty STs (55.56 %) and six alleles among them were first detected. Virulence genes including flaA, cadF, and the cytolethal distending toxin (CDT) gene cluster, were detected in all isolates, but truncated cdt gene clusters only detected in the isolates from the crow, daurian jackdaw and silver pheasant. In conclusion, it was the first detection of C. jejuni involved truncated cdt gene clusters from the silver pheasant. These wild birds around urban and suburban areas may pose potential public health problems as reservoir vectors of Campylobacter jejuni.